Emprego de lipases na resolução cinética de ésteres alquinílicos para produção de alquinilcarbinóis quirais - Almeida, Diana Kelly Castro de (2021)
Polyacetylenic compounds are secondary metabolites biosynthesized by different organisms, among which are species of marine sponges, which have in their structures one or more alkynylcarbinolic units. These compounds are noteworthy for their high activity against cancer cells. In this project we describe the study of the enzymatic kinetic resolution (EKR) of five racemic alkynylcarbinols acetates, via lipase-catalyzed hydrolysis reaction, to produce the enantiomerically pure or enantioenriched alkynylcarbinols. Therefore, rac-heptadeca-1,4-di-in-3-yl acetate (rac-2-Ac) was used as a “model” substrate in the study. After screening, the lipase of C. antarctica B immobilized on acrylic resin (CAL-B) was selected, which led to a conversion value of 50%, values of enantiomeric excess of alcohol and acetylate >99% and enantioselectivity (E)> 200 in a reaction time of 48 h at 30 °C without co-solvent. Therefore, CAL-B was used to extend the EKR study of rac-heptadeca-1,4,6-tri-in-3-yl acetate (rac-3-Ac), rac-heptadeca-1-en-4-in-3-yl acetate (rac-4-Ac) and rac-heptadeca-1-in-3-yl acetate (rac-5-Ac). In all EKRs, CAL-B was more efficient in the presence of acetonitrile as a co-solvent, varying the time and temperature parameters to obtain the best results and thus producing (R)- and (S) alcohols with 50% conversions , enantioselectivities (E) 194->200 and high values e.e. [(R)-3 and (S)-3-Ac, e.e. 98%, at 7 h and 20 °C; (R)-4, e.e. 97% and (S)-4-Ac, e.e. 95%, in 3 h and 25 °C; (R)-5 and (S)-5-Ac, e.e. 96%, in 5 h and 25 °C). The rac- (tri-isopropylsilyl) penta-1,4-di-in-3-yl (rac-6-Ac) acetate is a versatile C5 dialquinylcarbinol (DAC) with a different carbon chain from the other rac-acetates (2, 3, 4 and 5) that had structures with 17 carbon atoms. For the substrate rac-6-Ac, in 24 h at 40 °C, the best conditions to obtain (R)-6 and (S)-6-Ac, e.e. >99% included the use of lipase T. lanuginosus (TLL) in the presence of tetrahydrofuran as a co-solvent. The ratio of enzyme: substrate of 2: 1 was used in all the EKCs of the racemic alkynylcarbinol acetates mentioned above. The (S) -alcohols were obtained by lipase-mediated hydrolysis of the (S)-acetate compounds, except for rac-2-Ac (chemical hydrolysis). The yields of pure or enantioenriched alkynylcarbinols (R and S) ranged from 39 to 88%.